Y-y1= m(x-x1)
y-2= -2(x+6)
y-2= -2x-12
y= -2x-10
Unless there is supposed to be a zero at the end of that 1, then the answer is no
So cancel each equation terms on both sides of the equation and move constant to the right side and change its sign. So your answer is A=-3
Your welcome
It is a pyramid. a polygon meets with a polyhedron and make a pyramid
Answer:
See attachment
Step-by-step explanation:
The given matrix equation is:
![0.5X = A.](https://tex.z-dn.net/?f=0.5X%20%3D%20A.)
To find Matrix X, we need to multiply both sides of the equation by 2 to obtain:
![2 \times 0.5X =2 \times A](https://tex.z-dn.net/?f=2%20%5Ctimes%200.5X%20%3D2%20%5Ctimes%20%20A)
This simplifies to;
![X = 2A](https://tex.z-dn.net/?f=X%20%3D%202A)
By scalar multiplication, we multiply each entry in the matrix A by to 2 to obtain matrix X.
The vertical stretch of f(x) to g(x) is a factor of 5
<h3>How to determine the dilation?</h3>
The functions are given as:
f(x) = x
g(x) = 5x
Substitute f(x) = x in g(x) = 5x
g(x) = 5f(x)
In th above equation, the factor is 5.
5 is greater than 1 (this means vertical stretch)
Hence, the vertical stretch of f(x) to g(x) is a factor of 5
Read more about dilation at:
brainly.com/question/3457976
#SPJ1